ОНОВЛЕННЯ ЗМІСТУ ВИЩОЇ ЕКОНОМІЧНОЇ ОСВІТИ В УКРАЇНІ НАПРИКІНЦІ XX СТОЛІТТЯ (Педагогіка вищої та середньої школи, 2004)
The article analyses the trends in development of higher éducation in Economies in Ukraine during the last decade of the XX century. It présents the innovations and improvements in curriculum of higher educational establishments, which trained specialists in the fïeld of Economies.